Reflexion sur la marginalisation de l’Eglise et des forces spirituelles - Joblin, Joseph (Gregorianum, 2017)
The autonomy from spiritual matters acquired by contemporary societies leads to an increasing marginalization of the Church and of those «idealistic forces» which make humanity progress by making superior values become real. The issue is thus the magnitude of this marginalization and if it is rejecting Christianity towards a past which will never return. The forms under which the Church is present to the world change in every era since, by virtue of their timeliness, they depend both on natural laws which command transformations of the world and on faith in Christ, who is to be met at the end of both personal and universal history, and therefore, does not reduce human beings to mere robots dependent on a power concerned only with satisfying their essential needs. This position, which was thought out by two 20th century theologians in particular, can also be found, for instance, in the words Pope Francis addressed to the Eucharistic Youth Movement on August 7, 2015.